TUGAS KESEHATAN KELUARGA DENGAN PERILAKU GAYA HIDUP LANSIA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS BINTAUNA KABUPATEN BOLAANG MONGONDOW UTARA - Rona Febriyona; Andi Nuraina Sudirman; Mutiya Datungsolang (Zaitun (Jurnal Ilmu Kesehatan), 2019)
Elderly is the final stage of human life cycle, is part of the life process that cannot be avoided and will be experienced by every individual. Therefore, in behaving in a healthy lifestyle, the elderly really need family support. The purpose of this study was to determine the Relationship of Family Health Tasks with Healthy Lifestyle Behavior of Elderly Patients with Hypertension in the Work Area of Bintauna Health Center. This type of research used quantitative research with descriptive correlation research with cross sectional methods. And the sampling technique using questionnaires to 100 respondents. Determination of the sample using Purposive Sampling. Data analysis using Chi Square Test. Results Showed Family Health Task with a good category of 78 respondents (95.1%) and less category 4 respondents (4.9%). And healthy lifestyle behaviors with a good category of 7 respondents (38.9%) and less categories of 11 (61.1%). The conclusion is that there is a strong correlation between family health tasks with healthy lifestyle behaviors in the elderly. The results were significant (p = 0,000 <a = 0.01).